The movement made us : a father, a son, and the legacy of a freedom ride - Dennis, David J., Jr; Dennis, David J., Sr (Harper an imprint of HarperCollinsPublishers, 2022)
"A dynamic family exchange that pivots between the voices of a father and son, The Movement Made Us is a unique work of oral history and memoir, chronicling the extraordinary story of the Civil Rights Movement of the 1960s and its living legacy embodied in Black Lives Matter. David Dennis Sr, a core architect of the movement, speaks out for the first time, swapping recollections both harrowing and joyful with David Jr, a journalist working on the front lines of change today. Taken together, their stories paint a critical portrait of America, casting one nation's image through the lens of two individual Black men and their unique relationship. Playful and searching, anxious and restorative, fearless and driving, this intimate memoir features scenes from across David Sr's life, as he becomes involved in the movement, tries to move beyond it, and ultimately returns to it to find final solace and new sense of self--revealing a survivor who travels eternally with a cabal of ghosts. A crucial addition to Civil Rights history, The Movement Made Us is the story of a nation reckoning with change and the hopes, struggles, setbacks, and triumphs of modern Black life. This is it: the extant chronicle of why we live, why we move, and for what we are made."--Publisher's website.